Determination of Uric Acid in the Presence of Dopamine on the Activated Pencil Lead Electrode - Reza Majidi, Mir; Danandeh-Jenagharad, Mohammad (Asian Journal of Chemistry, 2016)
The electrochemical properties of uric acid and dopamine on the activated pencil lead electrode (APLE) have been investigated. Cyclic voltammetry was applied for activation of pencil lead electrode and differential pulse voltammetry (DPV) was considered as suitable procedure for determination of dopamine in the presence of uric acid. The effect of different parameters such as pH and composition of support electrolyte, range of potential, number of cycles has been investigated. On the APLE in optimum condition, anodic peaks of dopamine and uric acid shift to negative potentials. The peak current is linearly proportional to the bulk concentration in the range of 6.8 × 10–6–1.8 × 10–5 and 5.0 × 10–6 – 1.1 × 10–4 M for uric acid and dopamine, respectively. Correlation coefficient was calculated from linear regression 0.9992 for uric acid and 0.9958 for dopamine. The detection limit was 3.2 × 10–6 M for uric acid and 8.6 × 10–7 M for dopamine. The APLE was used for determination of UA in biological samples such as serum. The results obtained were compared with those of standard spectrophotometric method. No significant difference is observed at 95% confidence level between the results of two procedures. Dopamine in pharmaceutical samples was determined using standard addition procedure with APLE.